Публічне управління в системі організації державної влади в Україні - Саварчук, Юрій Миколайович; Savarchuk, Yuriy Mykolayovych (Ірпінь, 2023)
Дослідження розвитку публічного управління в системі організації державної влади в Україні з урахуванням сучасних вимог законодавства щодо публічного управління.

Study of the development of public administration in the system of organization of state power in Ukraine, taking into account modern requirements of legislation on public administration.
Public management in the system of organization of the state rule in Ukraine
Keywords: управління; система; державна влада; організація; специфіка; ефективність; management; system; state power; organization; specificity; efficiency